Central Romani and contributions to its structural description and dialectology. Introduction to the special issue of Romano džaniben - Elšík, Viktor (Romano džaniben, 2020)
Central Romani is a summary designation of those varieties of Romani that have been, or used to be, spoken by the long established Romani population of East Central Europe. The text introduces Central Romani from a dialectological perspective (including its division into the North Central and South Central groups); provides a detailed overview of descriptive sources (grammars, dictionaries etc.) as well as textual documentation; and outlines the perspectives of further research on Central Romani.
Keywords: Central Romani; North Central Romani; South Central Romani; language documentation; language description; dialectology